IMPLEMENTATION OF AUTHENTIC LEARNING MODEL IN SOCIAL LEARNING FOR DEPELOPMENT OF STUDENT’S SOCIAL SKILLS (Classroom Action Research at class of VII A in SMP Negeri 7 Bandung) - Purnamasari, Dian (Universitas Pendidikan Indonesia, 2016)
This study originated from the writer’s concern towards an issue occurred in seventh graders of SMP N 7 Bandung related to social skills of student. The issue is finding from conducted observation in several meetings of February 2014. Indicator of the problems which is encountered is low interest in cooperating, responsibility and tolerance of learners in learning process, less understanding of the meaning of social studies, low participation of learners in learning, unwell paradigm of social studies, lack of initiative participation in learning process, and low learning results. Reviewing the examined issues relate to the learning process, the researcher chose Classroom Action Research (CAR) with 4 cycles of David Hopkins research design. Alternative selected solutions, namely Authentic Learning Models. Implementation of authentic learning activities in social learning as an alternative in purpose to develope the social skills of students can be categorized in good level. The development of authentic learning in social learning can be seen from the development of social skills indicators such as able to cooperating with their groups, had a good responsibility, and able to apply owned knowledge, have perspective, empathized, and have self-knowledge to toleranced with others. Based on the findings in field could conclude from this study, including the first, well-designed research planning. Second, grow social skills of students in the implementation of the learning activities using utilization of authentic learning carried out more focused and neatly on each cycle. Third, reflecting the constraints that are found in every cycle and overcome the constraints on the next cycle. Fourth, the solution in the constraints found in the utilization of authentic learing students experience positive changes that increase students' social skills. This reflects the achievement of all indicators of students’social skills. Fifth, after using utilization of Authentic Learning able to grow social skills in students. Keywords: Authentic Learning, Social Skills